SUMO polymeric chains are involved in nuclear foci formation and chromatin organization in Trypanosoma brucei procyclic forms - Iribarren, Paula Ana (2018)
SUMOylation is a post-translational modification conserved in eukaryotic organisms that involves the covalent attachment of the small ubiquitin-like protein SUMO to internal lysine residues in target proteins. This tag usually alters the interaction surface of the modified protein and can be translated into changes in its biological activity, stability or subcellular localization, among other possible outputs. SUMO can be attached as a single moiety or as SUMO polymers in case there are internal acceptor sites in SUMO itself. These chains have been shown to be important for proteasomal degradation as well as for the formation of subnuclear structures such as the synaptonemal complex in Saccharomyces cerevisiae or promyelocytic leukemia nuclear bodies in mammals. In this work, we have examined SUMO chain formation in the protozoan parasite Trypanosoma brucei. Using a recently developed bacterial strain engineered to produce SUMOylated proteins we confirmed the ability of TbSUMO to form polymers and determined the type of linkage using site-directed mutational analysis. By generating transgenic procyclic parasites unable to form chains we demonstrated that although not essential for normal growth, SUMO polymerization determines the localization of the modified proteins in the nucleus. In addition, FISH analysis of telomeres showed a differential positioning depending on the polySUMOylation abilities of the cells. Thus, our observations suggest that TbSUMO chains might play a role in establishing interaction platforms contributing to chromatin organization.